Pembangunan Persiapan ISO 9001:2015 Pada Sistem Manajemen Mutu Rumah Sakit Berbasis Web (Studi Kasus : Rumah Sakit Umum Daerah Gambiran Kota Kediri) - Dimas Raynaldo Dwi Putra; Faizatul Amalia; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
ISO certification is one of the certifications that have become the standard for Gambiran Kota Kediri Regional General Hospital (RSUD) related to service quality assurance services. RSUD Gambiran Kota Kediri wants to change the ISO 9001: 2008 certification to ISO 9001: 2015 to improve the quality management system. Problems in Gambiran Hospital related to preparation for ISO 9001: 2008 certification are documentation management. Many documents are difficult to find and search documents. While these documents can be used and needed at any time. The funds allocated for ink and paper are also fairly small allocated. The next problem is the distribution of documents by giving to each related unit. The distribution process that is still done manually like that will take a lot of time and effort. In this study, a simulation system for the preparation of ISO 9001: 2015 certification was developed that is expected to help debate that takes place at Gambiran Hospital. System development is done by using a waterfall. Software testing is carried out using five tests, including integration testing and unit testing with the white-box testing method, for testing using the black-box testing method, namely validation testing, compatibility and usability testing. Unit testing concluded six test cases in the form of results, namely valid status and integration testing concluded two test cases with valid status. The validation test concluded that the results of 94 test cases with the status of all test cases were valid. Compatibility testing shows browsers that work on the system. Usability testing produces a score of 78.75 which indicates the system can be accepted by the user.